Interprofessional Education Context Analysis of a University in Ghana - Amn Bening; Victor Mogre; Yolande Heymans; Christmal Dela Christmals (Jurnal Ilmu Pendidikan, 2025)
The benefits of interprofessional education, including helping health professionals to develop good interpersonal relations with other professionals, improved acquisition and retention of competencies, improved patient care outcomes, cost-effective care, and improved healthcare professional job satisfaction, outweigh the inputs needed to develop and implement it. The processes for developing and implementing IPE program vary from institution to institution because of the strong influence of the context on IPE program. A context analysis is therefore paramount in developing IPE program. This study presents the findings of a context analysis of a university, using qualitative descriptive research methods supported by semi-structured interviews. A total of 25 participants participated in this study: ten (10) academics, two (2) support staff, and 13 students distributed across six programs were interviewed in this study. We found that facilitators such as an already existing interdisciplinary module across all health professions, the interprofessional nature of the student population, existing collaborative practices, and the availability of resources that can be used for IPE give the university advantages. Meanwhile, challenges such as inadequate personnel, inadequate resources, and lack of IPE policy or program impede the development and implementation of IPE in the university. Leveraging the support of the Africa Interprofessional Education Network and other universities that have implemented the IPE programmed to develop and implement the IPE program will be essential. Finally, regulatory bodies should engage stakeholders in inserting IPE competencies as a require followed by for accredit after professions education programs in Ghana.